2021
DOI: 10.30574/wjarr.2021.9.2.0060
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with cognitive developmental delay among infants attending Reproductive and Child Health clinics in Dar es salaam, Tanzania

Abstract: Background; Early child cognitive development is important throughout one’s life span. It is estimated that more than 200 million children under five years of age fail to achieve full cognitive development in the world and 80% of them are in south Asia and sub-Sahara-Africa. Genetic and environmental factors play a role in early child development (ECD). Most of the ECD occurs in the first 2years of life, but largely during infancy. Malnutrition, poverty and poor health care to children have been found to have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 52 publications
(61 reference statements)
0
3
0
2
Order By: Relevance
“…In a study among 3-to 4-year-old children in UNICEF's Multiple Cluster Indicators Surveys in 51 middle and low-income countries found 10.1% had significant cognitive delay and in 73 middle and low-income countries found 9.7% had significant cognitive delay (5,13). Another study among infants aged 1-12 months attending Reproductive and Child Health clinics in Dar es salaam, Tanzania in 2012 reported the Proportion of infants with cognitive developmental delay was 12.3% (14). A study in North India from 2011 to 2013 among 12-30 months old toddler observed nearly one-fifth (17.3%) of the toddlers had cognitive delay (15).…”
Section: Discussionmentioning
confidence: 99%
“…In a study among 3-to 4-year-old children in UNICEF's Multiple Cluster Indicators Surveys in 51 middle and low-income countries found 10.1% had significant cognitive delay and in 73 middle and low-income countries found 9.7% had significant cognitive delay (5,13). Another study among infants aged 1-12 months attending Reproductive and Child Health clinics in Dar es salaam, Tanzania in 2012 reported the Proportion of infants with cognitive developmental delay was 12.3% (14). A study in North India from 2011 to 2013 among 12-30 months old toddler observed nearly one-fifth (17.3%) of the toddlers had cognitive delay (15).…”
Section: Discussionmentioning
confidence: 99%
“…Berbagai aspek dapat mempengaruhi gangguan perkembangan kognitif anak. Usia anak, kehadiran pengasuh, dan wasting secara signifikan terkait dengan keterlambatan perkembangan kognitif (Gudila Valentine Shirima et al, 2021). Wasting merupakan kondisi dimana anak mengalami penurunan berat badan yang terus menerus.…”
Section: Pendahuluanunclassified
“…Studi tersebut juga menjelaskan bahwa bayi membutuhkan ibu untuk menghabiskan waktu bersama mereka dan pencegahan malnutrisi berperan dalam perkembangan kognitif. Studi lain juga memperjelas kondisi ini dengan melaporkan bahwa penting bagi ibu untuk hadir menemani anak sepanjang hari (Gudila Valentine Shirima et al, 2021). Ketidakhadiran ibu terutama pada siang hari, memungkinkan 12 kali lebih mungkin bagi bayi untuk mengalami keterlambatan perkembangan kognitif dibandingkan yang tidak.…”
Section: Pendahuluanunclassified
“…(Sepeku & Kohi, 2011;Mangu et al, 2021) the prevalence rate of DDM was 2.3%; among children aged five years and above, overall 7.8% of females had DDM compared to 5.7% of males (Murphy et al, 2020). The frequency of newborns with cognitive developmental delay, on the other hand, was found to be 12.3% in a Dar es Salaam (Shirima., 2013). Studies conducted in Morogoro and Manyara also revealed that the main factors of DDM in cognitive, communication and motor domains were poverty malnutrition and inadequate skills among health care providers in primary health care level (Sudfeld et al, 2015;Ribe et al, 2018 ;MOHCDGEC., 2022).…”
Section: Introductionmentioning
confidence: 98%
“…The gap increased from 19.1% to 31.4% (Kim., 2022). According to (Gil et al, 2020) the incidence of DDM varied by region, ranging from 10% in Europe and Central Asia to 42% in West and Central Africa (Padayachee & Ballot, 2013;Shirima, 2013;Oluwafemi et al, 2018;Abdel et al, 2018;Sunderajan & Kanhere, 2020;Saleem et al, 2020). The situation is worse for children born under a variation of medical conditions, including BA (WHO, 2011; Shaahmadi et al, 2015;Boskabadi et al, 2015 ;Lee et al, 2019 ;Lancaster et al, 2018).…”
Section: Introductionmentioning
confidence: 99%